The challenge of motivated cognition in promoting lake health among shoreline property owners: biased estimation of personal environmental impact. (1st October 2016) - Amato, Michael S.; Shaw, Bret R.; Olson, Eric; Turyk, Nancy; Genskow, Ken; Moore, Colleen F.
ABSTRACT: Amato MS, Shaw BR, Olson E, Turyk N, Genskow K, Moore CF. 2016. The challenge of motivated cognition in promoting lake health among shoreline property owners: biased estimation of personal environmental impact. Lake Reserve Manage. 32:386–391. Habitat loss through shoreline development on inland lakes threatens biodiversity. Property owners can reduce their impact by growing vegetated shoreline buffers, but many do not adopt these land management behaviors. One factor that may influence individuals' decisions to participate in conservation initiatives to promote natural shorelines is beliefs about their personal impact. A field study tested whether motivation to protect positive self-view would influence property owners' judgments about their shoreline's impact on lake health. Participants rated photos of their own property and other participants' properties on 4 dimensions: beauty, usability, water quality, and habitat. Linear mixed-effect modeling revealed photos were rated higher by their owners than other participants on all dimensions (mean β = 1.13, P < 0.05 for all), consistent with the hypothesis that motivation to protect self-view biased property owners to judge their own shoreline development as less harmful than it was judged by others. These results identify a potential barrier to outreach efforts for enlisting property owner cooperation in mitigating habitat degradation from shoreline development.